1992
DOI: 10.1007/bf02284961
|View full text |Cite
|
Sign up to set email alerts
|

Heating and cooling of the nitroglycerin patch application area modify the plasma level of nitroglycerin

Abstract: 19 healthy volunteers wore a nitroglycerin patch releasing 10 mg per 24 h for 2 h. Subsequently, the skin area surrounding the patch was exposed to 15 min of local heating with an infrared bulb (Group A, n = 10), or local cooling with an ice-pack (Group B, n = 9). The patch was protected by an insulating shield (Styrofoam). After 10 min of heating, the median (Walsh) plasma nitroglycerin level increased from 3.1 to 7.6 nmol.l-1. Body temperature remained constant. After 15 min of cooling the median plasma leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Under in vivo conditions, the increase in blood supply to the surface of the skin as a result of increased temperature also plays an important role in enhancing the transdermal delivery of a topically applied compound (Klemsdal, Gjesdal, and Bredesen 1992;Hull 2002). The in vivo delivery of nitroglycerin (Klemsdal et al 1992), testosterone, lidocaine, tetracaine (Shomaker, Zhang, and Ashburn 2001) and fentanyl (Ashburn et al 2003) from transdermal patches with attached heating devices was shown to increase as a result of the elevated temperature at the site of delivery. However, the effect of temperature on the delivery of penetrants over 500 Da has not been reported.…”
Section: Temperature ("Thermophoresis")mentioning
confidence: 99%
“…Under in vivo conditions, the increase in blood supply to the surface of the skin as a result of increased temperature also plays an important role in enhancing the transdermal delivery of a topically applied compound (Klemsdal, Gjesdal, and Bredesen 1992;Hull 2002). The in vivo delivery of nitroglycerin (Klemsdal et al 1992), testosterone, lidocaine, tetracaine (Shomaker, Zhang, and Ashburn 2001) and fentanyl (Ashburn et al 2003) from transdermal patches with attached heating devices was shown to increase as a result of the elevated temperature at the site of delivery. However, the effect of temperature on the delivery of penetrants over 500 Da has not been reported.…”
Section: Temperature ("Thermophoresis")mentioning
confidence: 99%
“…The increased permeation following heat treatment has been attributed to an increase in drug diffusivity in the vehicle and an increase in drug diffusivity in the skin due to increased lipid fluidity (57). Vasodilation of the subcutaneous blood vessels as a homeostatic response to a rise in skin temperature also plays an important role in enhancing the transdermal delivery of topically applied compounds (58,59). The in vivo delivery of nitroglycerin (58), testosterone, lidocaine, tetracaine (60) and fentanyl (61) from transdermal patches with attached heating devices was shown to increase as a result of the elevated temperature at the site of delivery.…”
Section: Temperature ("Thermophoresis")mentioning
confidence: 99%
“…11 Heat-induced local vasodilatation and acceleration of skin blood flow appear to be the main mechanisms leading to this change in absorption. 12 Vanakoski and Seppälä 11 also state that, "changes in the physicochemical properties of transdermal patches, sweating and increased humidity of the skin may contribute to the release and diffusion of transdermally administered drugs".…”
Section: Climate and Pharmacokineticsmentioning
confidence: 99%